Understanding tourists' motivation on wellness center in Malaysia - Yong, Zi Yee (2023)
Since the restrictions were lifted following Covid-19, the number of people visiting wellness centres has gradually increased. Thus, this paper investigates the tourists’ motivation on wellness center in Malaysia. It is found out that the there are several reasons that leads tourists to visit wellness center in Malaysia. Researchers has identified that Malaysian tourists are affected by the factors such as attitude, subjective norms, perceived behavioral control, cultural aspect, relaxation, satisfaction in experience and destination loyalty. Researchers will explain about the dependent variable and each of the independent variable in the literature reviews. The primary data were collected using google form. The sample size of the research is 300 respondents, and the targeted area is Klang Valley. Moreover, research instruments and construct management will be used to carry out the research. Researchers will also use the Smart PLS 4 to run the collected data form the survey questionnaires, and proceed with data processing and analysis. An interpretation of the result will be explained by the researcher using tables and graph. Lastly, researchers will provide recommendation and detect the limitation throughout the whole research. This is to provide contribution for academics who are interested in the related field and tends to get a deeper understanding of the study. It also helps the organization in Malaysia to understand the need and wants of the tourists while visiting wellness center in Malaysia.